Chapter 2 Dynamics of Incubating a Multi-community, Multi-commodity, Multi-location, FPO The Case of Krishidhan Producer Company in Gujarat - Pastakia, Astad (Taylor & Francis, 2023)
Krushidhan Producer Company Ltd. (KPCL) was incubated by the Development Support Centre (DSC), Ahmedabad. Registered in December 2013, KPCL caters to about 40,000 farmers from 190 villages in four districts, where it was increasingly becoming unviable to practice agriculture. DSC worked in three phases, first establishing an agri-extension system, then forming the company, and finally helping it become financially independent over 6 years. By 2020-21, the company was serving 18,400 farmers - 4409 shareholders and 14,000 non-members. Its share-capital stood at Rs. 4.406 m and its turnover at Rs. 85.0 m. KPCL's success tells us the story of how community mobilization and building social capital of the community in the form of SHGs, Kisan clubs, etc. can lead to a strong institution. It was able to draw on resources from its members to carry out its activities, in the absence of formal credit. This brings out the social nature of FPOs, and needs to balance its social goals with commercial viability. Given its multi-location, multi-community and multi-commodity nature, Krushidhan presents lessons for many similar producer organizations.